Implementation and Experiment of a Novel Molecular Spring Isolator - Gaofa Nie; Xuhong Miao; Yuhang Tang; Qian Chen (Shock and Vibration)
A molecular spring isolator comprising ZIF-8 with hydrophobic micropores, water, and a cylinder/piston unit is introduced. Liquid water can be intruded into the micropores of ZIF-8 under critical pressure. In the meantime, mechanical energy is stored. And once the external pressure is withdrawn, spontaneous capillary evaporation will occur. The stored energy, meanwhile, is released. This behavior is similar to a coil spring. The Laplace–Washburn equation is used to describe the force equilibrium of a single water column in a micropore. After that, the result of water infiltrating a great deal of hydrophobic pores is revealed by theoretical analysis and an experiment. An averaging method is devoted to computing the primary resonance response and its accuracy is proved by the fourth-order Runge–Kutta method. Furthermore, the energy transmissibility is used to estimate its vibration isolation capability. Finally, a vibration isolation test indicated that the inherent frequency of the isolator is as low as 1.3 Hz.